The Effect of Parenting Styles on Child Malnutrition: Pengaruh Pola Asuh Orang Tua terhadap Gizi Buruk pada Anak - Elisabet Andriani Imus; Karmelia Rosfinda Meo Maku; Efrida Ita; Yanuarius Ricardus Natal (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2026)
This study aims to understand the influence of parenting patterns on malnutrition in children, specifically to identify and address factors that can cause malnutrition problems in children. Proper parenting is very important to ensure that children receive adequate nutrition and grow optimally. The urgency of this research is very high because parenting is a dominant factor affecting children's nutritional status, even more than just economic factors. This study uses a quantitative method, an approach conducted by the researcher using numbers and formulas, so data collection in this study includes observation, pre-test, post-test, and documentation. The results of the study indicate that in the Kisanata sub-district, there are children experiencing stunted growth compared to children of the same age. According to growth observations, the development experienced by the children is very slow, with weight not meeting the standards and several other problems.